Analisis keterdedahan risiko syariah syarikat pengendali takaful di Malaysia / Mohd Faiz bin Mohamed Yusof - Mohd Faiz, Mohamed Yusof (2017)
Takaful Operator is an Islamic financial institution licensed as a sharī’ah compliant financial institutions by Central Bank of Malaysia. The takaful industry in Malaysia is exposed to sharī’ah risks due to the sharī’ah compliance requirements in all operations and activities of the Takaful Operator. Sharī’ah risk exposures generally occur because of the elements that not comply with sharī’ah requirements such as riba, gharar, gambling, ghubn, ikrāh, taghrīr and ghalaṭ or any element that was not comply with sharī’ah by the sharī’ah regulatory whether Sharī’ah Committee of Takaful Operators or Sharī’ah Advisory Council of Central Bank of Malaysia. However, the complicated of activities and operation by Takaful Operators, will exposed to Sharī’ah risk due to certain weaknesses such as staff, operations, system and sharī’ah governance. The objective of this study to identify and analyse the sharīah risk exposures in Malaysia Takaful Operators This study will use qualitative approach with semi-structured interviews by 11 informants which are involved in managing sharī’ah compliant in Malaysia Takaful Operators. Computerized program ATLAS.ti 7 was used in this qualitative study to organize, analyze and display the results of this study. The findings show that there are 18 aspects of shariah risk exposures in Malaysia Takaful Operators includes inadequacy of shari’ah resolution aspects, errors and mistakes by staff and agents, weakness in internal operation and the lack of sharī’ah governance process. The study also describes the approach to manage sharīah risk exposures in Malaysia Takaful Operators, mostly managed through the role of Sharī’ah Department of Takaful Operator, Sharī’ah Committee of Takaful Operators and the process of sharī’ah review.